#TITLE_ALTERNATIVE# - LUQMANUL HAKIM (NIM 10104014), MUH.
Frame of subspace is a sequence of pairs of closed subspace in separable Hilbert space with number in L~, and its sequence have a specialization. This specialization makes the sequence can be said as frame of subspace or not. We can see, that this sequence can be said as frame of subspace, by see the specialization of its closed subspace and its number. In this book, describe some specializations of its closed subspace and its number, to get the sequence that can be said as a frame of subspace.